Functional Cereal Foods for Health Benefits: Genetic and/or Processing Strategies to Enhance the Quali-Quantitative Composition of Bioactive Components - Laddomada, Barbara; Wang, Weiqun (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Cereal foods comprise a large variety of products that make up the main part of the diet of the world population. Despite decades of research to improve cereals and cereal food quality, worldwide research coordination is now required due to market needs, processing, and climate change. Cereals and cereal foods are an important source of energy (carbohydrates, proteins, and fat), and offer a range of non-nutrient bioactive components (i.e., vitamins, minerals, dietary fiber, and phytochemicals) that provide different grades of health benefits. The main challenges for the near future include the exploration, valorization, and improvement of genetic variation for nutrients and bioactive food components; the use and implementation of biotechnological, preprocessing, and processing strategies to improve content; and the evaluation of health properties for health claims.